DISCOURSE ANALYSIS OF UNDERGRADUATE STUDENTS' ARGUMENTATIVE WRITING IN HIGHER EDUCATION: STRUCTURE, STANCE, AND PERSUASION - Dewi Afriany Susanti; Tina Sheba Cornelia Sitompul (Sensei International Journal of Education and Linguistic, 2024)
Argumentative writing is an important skill for students in higher education, but many students still find it difficult. This study discusses the discourse of students' argumentative writing in higher education. The study used a qualitative descriptive method with discourse analysis. The data were students' argumentative essays. The essays were analyzed based on argument structure, metadiscourse, and stance. The result shows that students can write claims and reasons, but they are still weak in warrant, backing, and rebuttal. Students also use more boosters than hedges, so their arguments sound too strong. Based on the result, it is suggested that lecturers teach argumentative writing explicitly so that students can write better argumentative essays.